Flowing Futures: Innovations in WASH for Sustainable Water, Sanitation, and Hygiene - Kumar, G. Mahesh; Chaturvedi, Prateek; Rao, A. Kakoli; Vyas, Manish; Sethi, Vandana Arora; Swathi, B.; Jabbar, Kadim A. (E3S web of conferences, 2023)
The future of Water, Sanitation, and Hygiene (WASH) entails a combination of urgent difficulties and unparalleled prospects. In the pursuit of achieving universal access to clean water and sanitation, together with the promotion of sanitary practises, innovation has emerged as a crucial driver for sustainable advancement within the global society. The present study, entitled “Flowing Futures: Innovations in Water, Sanitation, and Hygiene (WASH) for Sustainable Provision of Water, Sanitation, and Hygiene,” examines the ever-changing terrain of WASH by examining novel approaches, with the ultimate goal of visualising a future in which all individuals have equal and fair access to these essential human entitlements. This study focuses on the convergence of WASH (Water, Sanitation, and Hygiene) with technology, emphasising advancements in water purification, sanitation infrastructure, and interventions targeting behaviour change. This study investigates the impact of recent improvements in data analytics, remote sensing, and smart infrastructure on the monitoring and management of water resources. These technological developments have the potential to significantly improve efficiency and enable prompt response during times of crisis. Also, the initiative known as “Flowing Futures” places significant emphasis on the importance of community-led strategies, acknowledging that the establishment of sustainable solutions is contingent upon local empowerment and active participation. This study examines many case studies from different geographical areas, demonstrating the significant effects of participatory programmes that enable communities to assume responsibility for their water, sanitation, and hygiene (WASH) services. These initiatives also promote a sense of stewardship towards the environment.